Socioeconomic development and human well-being - Khatun, Masuma; Tarannum, Sabah; Hyder, S.M. Ziauddin (BRAC Research and Evaluation Division (RED), 2019)
Since 1992, BRAC and ICDDR,B have been implementing a joint research project in Madab, Bangladesh to assess the pathways of impact of BRAC's dewlopmcnt interventions on human wen-being. The project identified improved mmi1ioDal status as one of the components of human wen-being. This report cbiumcnts the nutrition component of the second round seasonal SUl'Vey findings conducted during mid September to December 1995 using the four-ceD survey design. A total of 2076 households were inteMewed to collect data on household food security, infant and chUd feeding prac1iccs and on an1hropometly. Data on preceding one week's household food intlow and outflow were collected to descn"be food security at the household J.evd. The anthropometric 8UI'WY was conducted for an household members aged 6 month and ~- Data on different parameters arc shown in the report stratified by BRAC member, BRAC eligible nonmember and BRAC non cHgiblc non-member.